“Spirituality” in Psychology: a Philosophical and Methodological Analysis - Vorobyeva, L.I. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2019)
The article problematizes the use of the concept of “spirituality” in psychological discourse, which loses its nuclear cultural meaning here while meeting the requirements of science. The author shows that this loss occurs in a necessary way and is connected with the epistemological foundations of modern science, namely, with the understanding (“model”) of “truth”. Consequently, a constructive prerequisite for the natural inclusion of “spirituality” in any discursive system may be a different model of truth in comparison with science. M. Foucault reveals three historical types of discursive practices where “spirituality” (unlike scientific discourse) was not a foreign concept: there ‘truth’ was defined as directly related to the sociocultural production of human subjectivity. Such discourses always implied anthropopraxis, where the condition for the attainment of truth was the “transformation” of its very subject — here ‘truth’ was semantically closely intertwined with the ethical category of “the good”. В статье проблематизируется употребление понятия «духовность» в психологическом дискурсе, которое при соблюдении требований научности утрачивает здесь свой ядерный культурный смысл. Автор показывает, что эта утрата происходит необходимым образом и связана с самими эпистемологическими основаниями нововременной науки, а именно — с пониманием («моделью») «истины». Следовательно, конструктивной предпосылкой для органичного включения «духовности» в какую- либо дискурсивную систему может стать иная в сравнении с наукой модель истины. М. Фуко выявляет три исторических типа дискурсивных практик, где «духовность» (в отличие от научного дискурса) не была инородным понятием: там «истина» определялась как непосредственно связанная с социокультурным производством человеческой субъективности. Здесь речь всегда шла об антропопраксисе, где условием достижения истины являлось «преображение» самого ее субъекта — в таких дискурсах «истина» семантически тесно переплетена с этической категорией «блага».